Development of Image Processing Algorithm for Array processor (International Journal of Engineering and Computer Science, 2017)
Mathematical morphology is a well known image and signal processing technique. However, most morphological tools such as Matlab are not suited for strong real-time constraints. This paper address this problem through hardware implementation on Array processor.This paper gives the algorithm of morphological image processing on FPGA/ Array Processor.